Intergenerational transmission of violence and resilience in conflict-affected Burundi: a qualitative study of why some children thrive despite duress. (20th December 2017) - Berckmoes, L. H.; de Jong, J. T. V. M.; Reis, R.
Abstract : Background: Research suggests that in environments where community conflict and violence are chronic or cyclical, caregiving can impact how children may begin to reproduce violence throughout the various stages of their lives. The aim of this study is to understand how caregiving affects processes of reproducing violence and resilience among children in conflict-affected Burundi. Methods: We combined a socio-ecological model of child development with a child-actor perspective. We operationalized the core concepts 'vulnerable household', 'resilience', and 'caregiving' iteratively in culturally relevant ways, and put children's experiences at the center of the inquiry. We carried out a comparative case study among 74 purposively sampled vulnerable households in six collines in three communes in three provinces in the interior of Burundi. Burundian field researchers conducted three consecutive interviews; with the head of the household, the main caregiver, and a child. Results: Our findings reveal a strong congruence between positive caregiving and resilience among children. Negative caregiving was related to negative social behavior among children. Other resources for resilience appeared to be limited. The overall level of household conditions and embedment in communities attested to a generalized fragile ecological environment. Conclusions: In conflict-affected socio-ecological environments, caregiving can impact children's functioning and their role in reproducing violence. Interventions that support caregivers in positive caregiving are promising for breaking cyclical violence.